DEVELOPMENT OF LKPD BASED ON PROJECT BASED LEARNING MODEL TO IMPROVE MATHEMATICAL CREATIVE THINKING ABILITY OF GRADE V ELEMENTARY SCHOOL STUDENTS - Astria Ayu Ramadianti; Edi Syahputra; R. Mursid R. Mursid (SENSEI RESEARCH CENTER, 2021)
This study aims to 1) analyze the validity of the LKPD based on the Project-Based Learning model on the flat side of cubes and blocks; 2) Analyzing the practicality of LKPD based on the Project Based Learning model; 3) Analyzing the effectiveness of LKPD based on Project Based Learning; 4) Analyzing the improvement of students' mathematical creative thinking skills through the development of LKPD based on the Project Based Learning model on the flat side of cubes and blocks. The subjects of this study were fifth-grade students of SD Negeri 101736 Medan Krio, while the object in this study was LKPD based on the Project Based Learning model. This type of research is development research with the Dick and Carey model. The results of this study indicate (1) Based on the results of the validity of material experts 89%, linguists 89.2%, and design experts 98.2%. From the results of the developed LKPD validation, the LKPD is included in the excellent criteria and is declared valid and feasible to use; (2) The project-based LKPD is categorized as practical because the results of the student's response to the LKPD obtained a value of 90.80%, namely if the student's response is greater than 80%, it is said that the student gave a positive response to the LKPD; (3) LKPD is effective because in the field trial the results of the percentage of classical completeness increased from 44.83% to 89.66%, positive student responses, and the percentage of effective learning time; (4) The students' mathematical creative thinking ability increased, the average score was 68.55 in the pretest, while the post-test average was 87.17